Heterogeneidade funcional edáfica e vegetacional no campo rupestre - Vanessa Matos Gomes (2020)
In chapter 1 we aimed to investigate whether Glomalin Related Soil Protein (GRSP), produced by arbuscular mycorrhizal fungi (AMF), reflects the heterogeneity of substrate and plant community in campo rupestre ecosystem. Soil samples were collected for physical-chemical and GRSP content analysis, in 40 plots, where the vegetation was also surveyed. GRSP content was compared between substrate types, and its relationship assessed against soil attributes, vegetation dissimilarity, and abundance of non-mycorrhizal species and of species less AMF dependent. GRSP content varied greatly among the sites, differed significantly between the ferrugineous and quartizitic substrates, and was related with soil organic carbon, soil nutrients, soil texture, and vegetation dissimilarity. The greater the cover of species presenting the sand-binding strategy besides the AMF association and of non-mycorrhizal species, the lower GRSP content. The study shows how the AMF, through GRSP, was 7 associated to the ecosystem heterogeneity. Results point GRSP as an important soil factor to be considered in management and conservation issues in the campo rupestre and similar ecosystems. GRSP content was shown to be linked to soil chemistry and physics, and shaped by cover variation of plant species less or non AMF dependent, reflecting the heterogeneous campo rupestre nature. In chapter 2 we developed a plant functional type (PFT) system to investigate the functional patterns of campo rupestre plant communities, in different substrate and habitat types. We sampled herbaceous and woody vegetation, as well as soil variables, in four habitats, among two substrate types (quartzitic and ferrugineous), and classified the species according to life-histories traits of relevance for ecological restoration. Functional dissimilarity was assessed among habitat and substrate types, and the role of soil factors in the dissimilarities was investigated. Pollination and seed dispersal syndromes, mycorrhizal association, and reproductive phenology were the main diagnostic traits defining the PFTs. We found distinct functional structure between plant communities of different substrate and habitat types, with influence of soil factors of both chemical and physical nature. Core PFTs were identified pointing main trait combinations represented in all or almost all habitats. We discuss about the singularities of each habitat in regard the PFT diagnostic traits, the identified core trait combinations, and the importance of functinal redundance when applying this knowledge to conservation and management actions.